2013
DOI: 10.30843/nzpp.2013.66.5706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spray deposition in potatoes using various spray delivery systems

Abstract: The tomatopotato psyllid incurs high control costs through intensive spraying and other treatments A field study was conducted in March 2012 in Pukekohe New Zealand to evaluate the pesticide deposition potential of five different spray delivery systems The treatments included a conventional boom a canopy submerged drop sprayer combination a pneumatic electrostatic spraying system an airassisted rotary atomizer and a highvolume airassist boom Each system was calibrated for appropriate spray volume rates between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…For instance, if the AI is systemic the coverage is likely a nonissue; or if the weed species are shorter than the crop, electrostatics will prohibit the herbicide from reaching the actual target. The deposition of dye throughout the canopy was consistent with the findings of Roten et al (2013) where similar patterns coverage were observed between all sprayers ( Table 2). The previous K-card work (Roten et al 2013) observed less coverage than expected with the DropSpray® system.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…For instance, if the AI is systemic the coverage is likely a nonissue; or if the weed species are shorter than the crop, electrostatics will prohibit the herbicide from reaching the actual target. The deposition of dye throughout the canopy was consistent with the findings of Roten et al (2013) where similar patterns coverage were observed between all sprayers ( Table 2). The previous K-card work (Roten et al 2013) observed less coverage than expected with the DropSpray® system.…”
Section: Resultssupporting
confidence: 86%
“…The deposition of dye throughout the canopy was consistent with the findings of Roten et al (2013) where similar patterns coverage were observed between all sprayers ( Table 2). The previous K-card work (Roten et al 2013) observed less coverage than expected with the DropSpray® system. The two most notable differences between the two datasets are that (1) the conventional boom applied 389% AI to the upper most canopy and leaf side, which is statistically different (P<0.05) from all other treatments and (2) the Proptec™ atomiser deposited greater amounts of AI on the lower leaf side of the upper canopy than would have been expected from the 7.6% coverage indicated in the previous study.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The utilization of the Dropleg ® bar support system aims at the enhancement of mixture accessibility at sites, such as the bottom part of the plant. Still considering that the system operates inside the canopy, a better drift control driven by wind action exists, as well as the possibility of varying the ratio between the amount of mixture sprayed through the Dropleg ® system and the conventional spray bar, as both can be adjusted according to the growth of the crop (Roten et al, 2013;Rüegg & Total, 2013).…”
Section: Resultsmentioning
confidence: 99%